The intersection of the HIV epidemic and blood donation in South Africa - Van Den Berg, Karin (Department of Medicine, 2025)
South Africa's large population of people living with HIV (PLWH) affects the local blood transfusion services (BTS) in multiple ways, including the recruitment of safe donors, the demand for blood and the development of blood safety policies. The latter includes the deferral of persons at risk of recently acquired HIV and sensitive testing for HIV antibodies and RNA. Estimating HIV incidence in blood donors is a key measure of successful prevention strategies. Blood donation by PLWH on antiretroviral therapy (ART) was identified as an emerging risk to blood safety as early ART initiation may result in delayed seroconversion, seroreversion, and prolonged suppression of viral replication which may escape detection by HIV antibody and nucleic acid amplification testing (NAT). My PhD research used epidemiologic, incidence modelling and mixed-method qualitative research techniques to assess the impact of undisclosed ART use among blood donors on the safety of the country's blood supply.